High expression of serine and arginine-rich splicing factor 9 (SRSF9) is associated with hepatocellular carcinoma progression and a poor prognosis - Guoshun Zhang; Bin Liu; Hua Shang; Guikai Wu; Diyang Wu; Liuqing Wang; Shengnan Li; Zhiyuan Wang; Suying Wang; Juxiang Yuan (BMC, 2022)
Highlights SRSF9 is a potential independent risk factor for HCC. High methylation status of cg06116271 predicted a better prognosis in HCC. SRSF9 knockdown inhibited the Wnt signaling pathway and cell cycle pathway. SRSF9 may serve as a potential therapeutic target for HCC.